Care Juice Bhd. - Benedict, Ed Gibson; Jopin, Rixdyvz Alyster; Rahiman, Calvin; Juatin, Shenna J.; Baramis, Fazri; Abduh, Mohd Syuwari (2014)
Our company is a new company which sells a health care juice which gives many benefits towards the customer. Our company name is Care Juice Bhd. This is the summary of our marketing plan. We are concentrating in targeting the market in Sepanggar until Sulaman area. In the marketing plan, we are concentrating in the 4P's concept which was the Product, Place, Promotion and Price. The vision of this company is to be to provide a good quality of juice that will exceeds our customer expectations and our mission is to be the best juice company ever. We are trying to provide a very beneficial product either to the customer or to the environment. Our company has set our product price based on profit oriented pricing which we use the profit maximization strategy. How price it, we look into the rival's price and we keep the status quo price of the market. We have several types of promotion strategies to our customer and distributor (wholesaler and retailer) including newspaper, mobile billboard, Facebook and websites, discounts, free sampling and loyalty programs. And our mean of distribution is through wholesaler and retailer channel. It will be placed on the several retail store and non store retailing. We have planed our budget and the total cost will be RM 103,100. The conclusion is we are giving our best to market our product so that we can achieve our stated goal and be a successful company. "Drink For a Better Tomorrow"